ANALISA WASTE PADA AKTIVITAS UPDATE MATERIAL DI DEPARTEMEN WAREHOUSE DENGAN MENGGUNAKAN METODE FMEA - Lokaputra, Riduwan; Kusuma, Egy Ardi; Widodo, Kukuh (Jurnal Sains Ilmu Teknologi Industri, 2023)
Warehouse is a place to store raw materials or finished goods. For manufacturing companies, raw materials are the main component in production. It is necessary to supervise and manage the availability of goods as well as to regulate the balance between supply of raw materials and demand for production. PT. ABC does not yet have a system for recording goods that is not yet optimal. The data collection process is done manually which results in a waste of time and money.Researchers assess PT ABC's material warehouse is not optimal, so it is necessary to make improvements in the control and management of raw materials that are supported by an information system. This is what underlies researchers to analyze waste reduction in updating material transfer locations using web-based application design using the FMEA method.